The genus Syzeton Blackburn, 1891 (Coleoptera, Aderidae) in the United States of America - Gompel, Nicolas (Zootaxa, 2022)
The species of Syzeton Blackburn, 1891 (=Zonantes Casey, 1895, syn. nov.) known from the United States are revised. All species formerly placed under Zonantes Casey, 1895 are transferred to Syzeton Blackburn, 1891: S. ouachitanus (Werner, 1990), comb. nov.; S. fasciatus (Melsheimer, 1846), comb. nov.; S. hubbardi (Casey, 1895), comb. nov.; S. nubifer (LeConte, 1878), comb. nov.; S. ater (LeConte, 1875), comb. nov.; S. pallidus (Werner, 1990), comb. nov.; S. subfasciatus (LeConte, 1875), comb. nov.; S. floridanus (Werner, 1990), comb. nov.; S. signatus (Haldeman, 1848), comb. nov.). Additionally, three new species are described herein: Syzeton gruberi n. sp., Syzeton arizonae n. sp., both from Arizona, and Syzeton belovi n. sp., from Texas, Oklahoma and Florida. Finally, Zonantes mississippiensis Werner, 1990 is considered a junior synonym of Syzeton ouachitanus (Werner, 1990), syn. nov.